The Relationship between Sleep, Chronotype, and Dental Caries—A Narrative Review - Anamaria Kurtović; Jasminka Talapko; Sanja Bekić; Ivana Škrlec (Clocks & Sleep, 2023)
This article provides an overview of how sleep and circadian rhythm disturbances mutually influence the occurrence of dental caries and how it is possible to reduce the risk of circadian rhythm disturbances, sleep, and associated adverse effects. Dental caries is a global problem worldwide that contributes to sociological limitations. Numerous factors influence the occurrence of dental caries, from socioeconomic factors to cariogenic bacteria, dietary habits, and oral hygiene. However, sleep disorders and circadian rhythm disturbances represent a new approach in the fight against the increasing prevalence of dental caries worldwide. Bacteria in the oral cavity and the oral microbiome are mainly responsible for the development of caries, and saliva plays an important role in their regulation. The circadian rhythm regulates numerous physiological functions, including sleep and saliva production. Disturbances in sleep and circadian rhythms affect saliva production, which impacts the development of dental caries, as saliva is necessary for regulating and maintaining oral health, especially for controlling oral infections. A person’s preference for a particular time of day depends on the circadian rhythm called chronotype. Individuals with an evening chronotype have a less healthy lifestyle that can lead to a higher caries risk than individuals with a morning chronotype. Because circadian rhythms are critical to maintaining sleep homeostasis and oral health, sleep disturbances can disrupt circadian rhythms and lead to a vicious cycle.